PENILAIAN KINERJA KARYAWAN PRODUKSI BERBASIS KEY PERFORMANCE INDIKATORS (KPI) - Revita Sholikha; Wahyu Eko Pujianto (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
This research aims to assess employee performance conducted on CV. Mitra Jaya's creation is to produce qualified and highly dedicated employees so that they get results in accordance with the target or can exceed the predetermined target. In this study, employee performance assessment used a strategy based on Key Performance Indicators (KPI). Every manager and company leader must be familiar with the so-called KPI. One of these management tools is a very effective tool to lift the performance of companies that want to scale up their business to a higher level. In addition to being simple and simple indicators used in KPIs, they are able to present business developments over time very clearly and specifically. This research uses a quality method. The results showed that there was a positive and significant influence on employee performance after the company implemented Key Performance Indicators (KPI) as an assessment of its performance. One of the benefits obtained is an increase in production results and weekly targets achieved even exceeding predetermined targets.